Peran Komunikasi Terapeutik Sebagai Upaya Rehabilitasi Kesehatan Mental Berbasis Komunitas - Palupi Nutia; Sri Wahyuningsih (Jurnal Keperawatan Muhammadiyah, 2026)
Background: Mental health remains an important yet often overlooked issue, especially in regions with strong cultural beliefs and stigma such as Sumenep Regency. Many people with mental disorders (ODGJ) have not received proper treatment and are still subjected to physical restraint. To address this issue, the Sumenep Community for People with Mental Disorders (KOPDAS) was established as a community-based initiative that focuses on therapeutic communication and social support in mental health rehabilitation. Objective: This study aims to identify and analyze the application of therapeutic communication in the rehabilitation process for people with mental disorders carried out by KOPDAS in Sumenep Regency. Methods: This qualitative research uses a case study approach to explore how therapeutic communication is implemented within KOPDAS activities. Data were collected through in-depth interviews, field observations, and documentation with purposive sampling selected informants consisting of KOPDAS founders, administrators, and active members. Data were analyzed interactively following Miles and Huberman’s model and validated through source and method triangulation. Results: The findings reveal that KOPDAS applies therapeutic communication through four stages based on Hildegard E. Peplau’s theory: pre-interaction, orientation, working, and termination. Each stage emphasizes empathy, active listening, and building trust between volunteers, patients, and families. This approach has effectively reduced social stigma, encouraged family participation, and accelerated patient recovery. Several patients previously restrained have successfully reintegrated into society and regained their social functions. Conclusion: Therapeutic communication serves as a key element in community-based mental health rehabilitation. By promoting empathy, collaboration, and sustained engagement between KOPDAS, community health centers, and local authorities, this model demonstrates an effective approach for improving mental health care in resource-limited and culturally sensitive settings.